Pengaruh Latihan Boot Camp terhadap Peningkatan Kemampuan Fisik, Koordinatif dan Prestasi Lari 200 Meter pada Siswa Putri - Zainab Qahtan Abdul Muhsin (Indonesian Journal of Physical Education and Sport Science, 2025)
Study Purpose. Through this instructional engagement, the researcher identified a noticeable deficiency in both physical and coordinative abilities, which appeared to adversely affect athletic performance particularly in the 200-meter sprint. This prompted the researcher to explore contemporary methods for enhancing these capacities. Among the approaches identified, Boot Camp training a high-intensity regimen emerged as a promising strategy capable of contributing effectively to this area of physical development. Materials and Methods. The researcher designed a boot camp training program targeting the enhancement of physical and coordinative skills among fourth-year female students. The program was applied, and its impact was measured through pre-and post-intervention assessments of the variables under investigation. Results. The findings revealed that boot camp training had a positive effect on the development of both physical and coordinative abilities. This improvement was also evident in the students’ enhanced performance in the 200-meter event. Conclusions. The study concluded that boot camp training is an effective method for improving physical and motor abilities, especially those related to event-specific sprint performance. Based on these results, the researcher recommends emphasizing fitness components associated with running and prioritizing the development of physical and motor capacities in female students’ training programs.